Retracted: Generalizing CTP: Does Probabilistic Routing in WSN Make Sense?. (14th November 2010) - Vilajosana Vilajosana, Xavier Xavier; Morell Morell, Antoni Antoni; Lopez Vicario Lopez Vicario, Jose Jose; Vilajosana Vilajosana, Ignasi Ignasi; Pacho Pacho, Jose Carlos Jose Carlos; Llosa Llosa, Jordi Jordi
Abstract : This article has been retracted as it is found to contain a substantial amount of material from the published paper "ZERO: Probabilistic Routing for Deploy and Forget Wireless Sensor Networks, " Xavier Vilajosana, Jordi Llosa, Jose Carlos Pacho, Ignasi Vilajosana, Angel A. Juan, Jose Lopez Vicario, and Antoni Morell, Sensors 2010, 10, 8920-8937; doi:10.3390/s101008920.